An Introduction to Corrosion Mechanisms and Models - Taylor, C.; Gale, Julian; Strehblow, H.; Marcus, P. (2015)
This chapter begins by introducing a series of corrosion mechanisms. It then discusses the principal modeling techniques used to represent and simulate these systems from the molecular perspective. The subsections in the chapter present a brief overview of contemporary approaches. As the brief survey that is made of the corrosion mechanisms reveals, there remain many more scientific and engineering problems that can be tackled via molecular modeling approaches. The combination of modern developments in computational architectures, algorithms, and molecular modeling approaches with the age-old problems presented by corrosion science (as well as emerging problems that develop as both existing and new materials are pushed to greater extremes) will no doubt continue to increase the application of these techniques to the field of corrosion science.